First human experience with catheter ablation using dipole charge density mapping integrated in robotics in the management of atrial fibrillation. (19th May 2022) - Gagyi, R; Noten, AME; Wijchers, S; Yap, SC; Bhagwandien, R; Hoogendijk, M; Szili-Torok, T
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Remote magnetic navigation (RMN) guided catheter ablation (CA) previously demonstrated high efficiency and efficacy in atrial fibrillation (AF) ablation. Heretofore, only the CARTO 3D mapping system was integrated in the RMN system. Recently, a novel high-resolution non-contact mapping system (AcQMap) can be used in combination with the RMN robotic system (AcQMap-RMN). Purpose: To assess efficiency, efficacy and safety of dipole charge density mapping in RMN guided ablation procedures for AF. Methods: All patients undergoing pulmonary vein isolation (PVI) or redo-PVI using the AcQMap-RMN system were analyzed. The AcQMap identifies different activation patterns such as focal firing, rotational activity, and localized irregular activation for substrate ablation. Procedural efficiency was characterized by procedure time, total ablation time and radiation doses. Efficacy data were based on 12-month follow up and number of redo procedures. Procedural safety was evaluated by intra- and post-procedural complications. Results: A number of 71 consecutive patients were included in the study (47 male, 24 female, mean age 60.8±9.9, 49 redo, 22 de novo). Twenty-four patients had paroxysmal (PAF), 47 had persistent AF (persAF). After completing PVI, 42 patients underwent AcQMap based substrate ablation. Twenty-four patients converted to atrial tachycardia/flutter during the ablation. The mean procedure time was 170.5±43.3 min, mean ablation time 1749.6±950.7 s, mean radiation dose was 207.0 (IQR 128.5 - 349.5) mGy. In the PAF group, radiation doses (128.5 vs 256.0 mGy, p=0.00) and application numbers (21.1 vs 37.0, p=0.00) were lower, ablation times were shorter (1312.5 vs 1919.3 s, p=0.02) compared to the persAF patient group. Two patients in the PAF group, and 9 patients in the persAF group had documented recurrence at the 6-month follow-up visits. In the PAF group, 23 patients were AF-free (95.8%), in the persAF group, 34 patients were AF-free at the end of the 12-month follow-up period (72.3%). Six patients had a redo procedure. Two patients were documented with hematoma, as minor post-procedural complication (2.8%). Conclusion: AcQMap-RMN integration provides high acute and long-term success rates, improved efficiency and low complication rates in paroxysmal and persistent AF ablation.